Famílias poliafetivas e simultâneas: uma análise a partir dos princípios constitucionais - CUNHA, Brenda Matos (2022)
Considering the lack of acceptance by the Brazilian legal system of simultaneous and poliafective relationships, the current research aims to analyze the difficulties faced by these family formations to be socially and legally accepted. In order that, it is necessary to address the constitutional principles that are applicable to family rights, the social role of the family nucleus today, the new models protected by Constitution of 88, the main similarities and differences between simultaneous and poliafective families and, then, how Brazilian indoctrinators and jurists have manifested themselves on this topic. Thus, it was done an exploratory survey with a deductive methodological approach and it was based on documentary and bibliographic research and analysis of decisions. To sum up, it was concluded that despite the legislative provision about the topic has not included them explicitly in the constitutional and infraconstitutional list, it is possible to give the protection constitutionally provided to the simultaneous and poliafective families based on the principles stablished by CFRB. As solution, it is argued the possibility of the jurisprudence, as well as it has already occurred in the legal field, stablishes a favorable position to the unions studied here, so it can incentivate a possible legal change or stablish an understanding that allows a fair and prejudice-free assessment of cases involving family simultaneity and poliafectivity.